2015
DOI: 10.1158/0008-5472.can-13-2190
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced SUMOylation of E3 Ligase HAF Determines Specific Activation of HIF2 in Clear-Cell Renal Cell Carcinoma

Abstract: Clear cell kidney cancer (CRCC) is initiated typically by loss of the tumor suppressor VHL, driving constitutive activation of HIF-1 and HIF-2. However, whereas HIF-1 has a tumor suppressor role, HIF-2 plays a distinct role in driving CRCC. In this study, we show that the HIF-1α E3 ligase HAF complexes with HIF-2α at DNA to promote HIF-2-dependent transcription through a mechanism relying upon HAF SUMOylation. HAF SUMOylation was induced by hypoxia, whereas HAF-mediated HIF-1α degradation was SUMOylation indep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…Stable cell lines overexpressing HAF and HAF DM (HAF K94R K141R) were generated by retroviral infection using pMX-IRES-GFP (20,24). 786-0 cells containing homozygous loss of HIF-2a (EPAS1): 786-0 EPAS1 À/À #4, EPAS1 À/À #11, and control (Nic Con) clones were generated using plasmids targeting different regions within exon 2 (sc400647-NIC, sc400647-NIC-2, or control double nickase plasmid sc-437281, respectively, from Santa Cruz Biotechnology).…”
Section: Plasmid Construction and Transfectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stable cell lines overexpressing HAF and HAF DM (HAF K94R K141R) were generated by retroviral infection using pMX-IRES-GFP (20,24). 786-0 cells containing homozygous loss of HIF-2a (EPAS1): 786-0 EPAS1 À/À #4, EPAS1 À/À #11, and control (Nic Con) clones were generated using plasmids targeting different regions within exon 2 (sc400647-NIC, sc400647-NIC-2, or control double nickase plasmid sc-437281, respectively, from Santa Cruz Biotechnology).…”
Section: Plasmid Construction and Transfectionsmentioning
confidence: 99%
“…Cells were lysed in cold cell lysis buffer with protease and phosphatase inhibitors, and Western blots were performed as described previously (20). Primary antibodies against phosphorylated or total proteins (EGFR, AKT, VEGFR, MEK, ERK, HIF-1a, HIF-2a) were from Cell Signaling Technology.…”
Section: Western Blots and Immunoprecipitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upstream stimulating factor-2 (USF-2) acts as a coactivator specifically for HIF-2α-dependent genes and is dispensable for the transcriptional induction of HIF-1α target genes (46). More recent work has identified that HIF-2α binding to SUMOlyated hypoxia-associated factor (HAF) increases its transcriptional activity, whereas HAF induces HIF-1α degradation, independently of SUMOlyation (47). In addition to coactivators, yin yang-1 (YY-1), a specific corepressor, directly binds and inhibits the transcriptional activity of HIF-2α (48) (Table 1).…”
Section: Oxygen-sensitive Transcription Factorsmentioning
confidence: 99%